Astragali Radix–Codonopsis Radix–Jujubae Fructus water extracts ameliorate exercise‐induced fatigue in mice via modulating gut microbiota and its metabolites. (31st March 2022) - He, Pan; Chen, Lei; Qin, Xuemei; Du, Guanhua; Li, Zhenyu
Abstract: BACKGROUD: Astragali Radix (AR) and Codonopsis Radix (CR) are widely used as the tonic herbal medicine with efficacy of tonifying qi in traditional Chinese medicine (TCM), which showed significant antifatigue activities. In this study, AR and CR were combined, with Jujubae Fructus (JF) further added to improve the taste, to afford the ACJ extracts in the ratio of 2:1:2. RESULTS: The results showed that ACJ water extract exhibited antifatigue effect by the weight‐loaded exhaustive swimming test in mice. The untargeted fecal metabolomic approach and 16S rRNA gene sequencing analysis showed that ACJ could improve exercise performance by regulating changes of gut metabolites and microbiota to alleviate fatigue. Four pathways were determined as the key pathways relating with its antifatigue effect, which included sphingolipid metabolism, glycerophospholipid metabolism, valine, leucine and isoleucine biosynthesis and d ‐arginine and d ‐ornithine metabolism. Correlation analysis showed the complex association among bacteria, metabolites and phenotypes. CONCLUSION: In conclusion, this study revealed new perspectives to study the antifatigue mechanism of ACJ extracts from the gut microbiota, which provided the basis for further functional food development. © 2022 Society of Chemical Industry.